Solar-Powered Peltier Thermoelectric Water Cooling and pH Monitoring - K. I. Jasmee; S. A. Jumaat (International Journal of Electrical Engineering and Applied Sciences)
This project focuses on the development of a solar-powered system for water cooling and pH monitoring using Peltier thermoelectric technology, specifically tailored for hydroponic applications. The system aims to maintain optimal water temperature and pH levels, which are critical for plant growth in hydroponics—ideally keeping water temperature below 29°C and pH levels between 5.5 and 6.5. The system design involves the integration of solar panels, Peltier modules, and sensors to achieve the desired cooling and monitoring functions. Simulation and hardware testing were conducted to validate the system's performance. Results showed that the system effectively maintained water temperature below 29°C and pH levels between 5.5 and 6.5, indicating its potential to support optimal conditions for hydroponic systems, which could contribute to improved crop management and resource efficiency. This research highlights the feasibility of using solar power as a renewable energy source for agricultural applications and demonstrates its potential as a sustainable approach to enhancing farming practices.